(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Medical research is a complex multi-disciplinary task involving specialists from different fields and professions, not only medical professionals. Medical databases are structured by information technology experts, but the contents must be tailored to the medical field. When the medical staff defines the information they use, terminology from their particular field of expertise is employed. This leads to misunderstandings between the maintainers and developers of information technology solutions, and the users of those solutions. When the time comes that a user, who is a medical professional, requires very specific data from the database, the chance of obtaining the data incorrectly is very high. By defining specific concepts and relationships between the data, in an explicit shared specification, some of the above problems can be avoided. The developed ontology-based data access system, described in this paper, provides a tool to store, manage and use definitions of common terminology and their mappings to the database. It is also capable of reasoning about the relationships between terms and indicates inconsistencies of term definitions, if any are present. By defining these interconnected terms in the ontology and by working through the system, all experts and software tools, who use the data, are able to use and reuse these terms to obtain data in a reliable and predefined way. This paper discusses the development and implementation of the ontology-based data access system, the ontology describing the medical data and the data mapping system, linking data from the database to concepts and virtual ontology individuals.